The development of intra-train beam stabilisation system prototypes for a future linear collider - Davis, MR (2014)
Any future linear collider requires a beam stabilisation system at the interaction point to the to maintain luminosities. This thesis details the development of prototypes of three such systems based at the Accelerator Test Facility 2 (ATF2) at KEK, Japan. The upstream feedback system utilises two stripline beam position monitors (BPMs) and two stripline kickers located in the ATF2 extraction line to stabilise the position and angle of the beam; the correction is then measured downstream at the ATF2 beam waist by a cavity BPM. The feedforward system uses the two upstream stripline BPMs to measure the position of the beam and calculate a correction signal which is then implemented locally by a stripline kicker located near the beam waist; the correction is then measured at the beam waist by a cavity BPM. The IP feedback system uses the position measured at the ATF2 beam waist by a cavity BPM and implements a correction based on this position using the local stripline kicker; the correction is then measured at the beam waist by a cavity BPM. Tests of the upstream feedback system have demonstrated stabilisation of the ATF2 beam waist at approximately the 300 nm level; tests of the feedforward and IP feedback systems have demonstrated stabilisation of the ATF2 beam waist at approximately the 100 nm level. Additional work undertaken to improve the processing electronics of the stripline BPMs is detailed. The cavity BPMs and their electronics are characterised and offline analysis techniques to improve the BPM resolutions set out. Results demonstrating resolutions of approximately 350 nm for the stripline BPMs and 80 nm for the cavity BPMs are presented.